2019
DOI: 10.1159/000499498
|View full text |Cite
|
Sign up to set email alerts
|

Association of MTHFR C677T, MTHFR A1298C, and MTRR A66G Polymorphisms with Neural Tube Defects in Tunisian Parents

Abstract: <b><i>Objective:</i></b> This study aims to investigate the association of 5,10-methylenetetrahydrofolate reductase (MTHFR C677T and A1298C) and methionine synthase reductase (MTRR A66G) gene polymorphisms with neural tube defects (NTDs) in a Tunisian population. <b><i>Methods:</i></b> Genotyping was performed by polymerase chain reaction with restriction fragment length polymorphisms (PCR-RFLPs) using the restriction enzymes. Allele and genotype frequencies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The results coincide with the previous studies by Wang et al9 in Chinese population and by Vandana Rai et al [23] in Eastern India (2019). In contrast study conducted by Nasri K et al [24] shows MTRR A66G is not associated with non-syndromic cleft lip and palate. There is geographical variation in the prevalence of MTRR A66G polymorphism.…”
Section: Discussionmentioning
confidence: 63%
“…The results coincide with the previous studies by Wang et al9 in Chinese population and by Vandana Rai et al [23] in Eastern India (2019). In contrast study conducted by Nasri K et al [24] shows MTRR A66G is not associated with non-syndromic cleft lip and palate. There is geographical variation in the prevalence of MTRR A66G polymorphism.…”
Section: Discussionmentioning
confidence: 63%
“…[ 29 30 31 32 ] Nasri et al ., in their study to find a possible association between MTHFR gene polymorphism and NTD in Tunisian parents found that, TT genotype and T allele in MTHFR C677T significantly decreased the incidence of NTDs in the mother group, but significantly increased this incidence in the father group. [ 33 ] A good deal ofinteraction occurs between Folate, Vitamin B12, Homocysteine and MTHFR [ Figure 7 ]. Richter et al .…”
Section: Discussionmentioning
confidence: 99%
“…Increased homocysteine level was found in homozygotes in polymorphism G80G in RFC gene and polymorphism T677T in MTHFR gene ( p < 0.05 compared with the G80G/C677C and G80G/C677T—genotypes) [ 53 ]. The risk of neural tube defects seems to be increased in MTHFR gene C677T polymorphism but may also be influenced by MTHFR gene polymorphisms A1298C and methionine synthase reductase gene polymorphism A66G [ 179 ]. Homozygotes in A1298C-genotype have higher levels of global DNA methylation ( p = 0.04) [ 147 ].…”
Section: The Main Clinical Syndromes Of Folate Deficiencymentioning
confidence: 99%